الجهاد البحري في حوض البحر الأبيض المتوسط وتأثيره في توجيه العلاقات الجزائرية الخارجية (إتفاقية 1795م أنموذجا) - دلال عطيت الله (جامعة محمد بوضياف بالمسيلة, 2025)
تهدف هذه الدراسة إلى تسليط الضوء على تطور البحرية الجزائرية خلال العهد العثماني، ودورها في حماية السيادة الوطنية، من خلال التركيز على "الجهاد البحري" بوصفه آلية دفاعية وهجومية أثّرت بشكل مباشر في العلاقات الجزائرية مع القوى الأوروبية، ثم لاحقًا مع الولايات المتحدة الأمريكية. وقد تناولت الدراسة نشأة وتطور الأسطول البحري الجزائري وبنيته، والعوامل التي ساهمت في قوته واستمراره، ثم حللت أثر المواجهات والاتفاقيات البحرية على التوازنات الإقليمية في حوض البحر المتوسط، وتُختتم الدراسة بتحليل اتفاقية الجزائر والولايات المتحدة الأمريكية عام (1209ه/1795م)، ودلالاتها السياسية والاقتصادية. This study aims to highlight the development of the Algerian navy during the Ottoman era and its role in safeguarding national sovereignty. It focuses on "maritime jihad" as both a defensive and offensive mechanism that significantly influenced Algeria’s relations with European powers and, later, the United States of America. The research examines the origins and evolution of the Algerian fleet, its structure, and the factors contributing to its strength and sustainability. It also analyzes the impact of naval confrontations and maritime treaties on regional balance in the Mediterranean. The study concludes with an assessment of the(1209/1795) treaty between Algeria and the United States, exploring its political and economic implications.